Financing higher education in the Islamic world through waqf (endowment) - Negasi, Mohamed Ibrahim (European Journal of Multidisciplinary Studies, 2017)
This study shows the meaning of waqf (endowment), its rule, pillars, and its classifications. Then it discusses in detail the contemporary application of the waqf in the financing of higher education from the Islamic point of view. The contemporary applications of waqf, assimilate cash Waqf (Waqf al-nuqood) that are used to finance the establishment and maintenance of higher education institutions, as well as providing the study and research materials for students and lecturers. It is also applied for endowment of books and software program that are relevant to the research and study. Also the endowment of libraries and equipment needed by laboratories, labs and libraries, as well as endowment of the rehabilitation research centers. The study uses the descriptive, the inductive and the analytical method. Based on the discussions and analyses, the study concluded that Waqf plays an effective and influential role in providing funding for higher education.